If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 17 = 12x + -79 Reorder the terms: 17 + 4x = 12x + -79 Reorder the terms: 17 + 4x = -79 + 12x Solving 17 + 4x = -79 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 17 + 4x + -12x = -79 + 12x + -12x Combine like terms: 4x + -12x = -8x 17 + -8x = -79 + 12x + -12x Combine like terms: 12x + -12x = 0 17 + -8x = -79 + 0 17 + -8x = -79 Add '-17' to each side of the equation. 17 + -17 + -8x = -79 + -17 Combine like terms: 17 + -17 = 0 0 + -8x = -79 + -17 -8x = -79 + -17 Combine like terms: -79 + -17 = -96 -8x = -96 Divide each side by '-8'. x = 12 Simplifying x = 12
| 9x^2+100x-2965550=0 | | 1-6q=-17 | | 3e^2(2x+1)=2e^2-e^2(x+1) | | 3p+2.5=3.7 | | a^2=7a | | (12x^2)+(12y^2)+3x+2y+6=0 | | 8x-y=5 | | v^2-5v=0 | | 13=-4.9t^2+13 | | x^5-5x^4-4x^3= | | 4x+3=3x-8 | | 4x-6=4(x+7) | | 0.4(x+300)=0.46x-348 | | 5(4x-9)-5=5(x-3)+70 | | x^2−7x+4=0 | | −7x+4=3x−5 | | 84=4x÷2 | | x2−7x+4=3x−5 | | x^2−7x+4=3x−5 | | Y=w^2+20w | | 4n+3=5 | | 4n+3=2 | | 36x^2+24=-4 | | 6n+8=10 | | 9=-r-5+11 | | 64x^2+32x=-4 | | 3n+2=6 | | 8y^2+26y+21=0 | | 6x^2*6x^4= | | -9.24-2.436= | | 9y^2=-27y | | -3.9-(-0.35)+8.6-8= |